Distributed vibration sensing for seismic acquisition - Dean, Timothy; Brice, T.; Hartog, A.; Kragh, E.; Molteni, D.; O'Connell, K. (Society of Exploration Geophysicists, 2016)
Distributed vibration sensing (DVS), also known as distributed acoustic sensing (DAS), is a relatively new method for recording seismic data using a standard fiber-optic cable as the sensor. Although the dynamic range and noise floor of DVS systems are currently below those of industry-standard seismic sensors, usable seismic data can be obtained in downhole configurations, as this is the source and receiver configuration at which DVS is most sensitive. The use of DVS for more conventional land and marine seismic acquisition is still some way off. However, the potential benefits of simple, lightweight fiber-optic cables, with fine spatial sampling and the ability to instrument all offsets of any spread, suggest it is worth pursuing these new applications. Permanent reservoir monitoring, particularly for marine environments, represents another application where the simplicity of fiber-optic sensors is attractive. Advances in laser interrogation techniques and signal processing continue to improve the quality of DVS data, increasing its potential applications across the seismic industry.